Theological faculties at the University of Strasbourg and the political role of Alsace in the interwar France - Ilya Rodin (Vestnik Pravoslavnogo Svâto-Tihonovskogo Gumanitarnogo Universiteta: Seriâ II. Istoriâ, Istoriâ Russkoj Pravoslavnoj Cerkvi, 2024)
The article is focused on the goals and circumstances of the restoring of the French university in Strasbourg in the context of the return of Alsace after the First World War, in particular, on the activities of two theological faculties – Catholic and Protestant. The activities of the renewed University of Strasbourg that represented the widest range of higher education programs in France due to the theological faculties, as well as its development during the whole interwar period were considered by the French authorities as an important part of the realization of the concept of “the French Alsace” and, so, of the entire French national idea. The particularities of the political role of the University of Strasbourg are discovered in the article by its characteristics as a self-regulated system on the base of special leaflets and periodical editions. The university opening report (1919), the reports on results of the scientific papers’ competitions (1921, 1922), the university guide for the foreign students (1922), the book dedicated to the history of protestant higher education in Strasbourg (1923), the overviews of the German press that were published in Strasbourg (early 1920s), the special issue of the newspaper «French Alsace» (1927) and the program of courses on the faculty of Protestant theology (1938) are among the analyzed sources. In addition to the listed materials, there are historical works on interwar University of Strasbourg represented by the special issue of the faculty of Catholic theology journal, published for the 50 years anniversary of its reopening, as well as several other articles.